The Teachers' Clinic. - Churchill, Nea C. (The Accounting Review, 1965)
Abstract The article presents the results of a recent survey conducted among schools which have made use of television in their accounting classes. The sole purpose of the survey was to provide a useful guide in deciding what course of action to recommend in regard to television instruction in accounting at schools. The report is designed to provide a general impression of the effectiveness of televised instruction, and a starting point for those who wish to investigate further in this regard. A majority of the schools surveyed were favorably impressed. Television for the instruction in accounting appears most applicable to the first-year course. With the use of student assistants during TV lecture periods and lab sessions, the student-teacher relationship appeared adequate. The use of uniform examinations for all TV course sections was overwhelmingly preferred to other examination methods. Some amount of released time is necessary for those preparing and conducting TV classes. Some additional types of visual aids, such as a VuGraph, are necessary and desirable. Maintaining normal class size as opposed to the lecture hall type of class was generally preferred.